Den hårdtslående fattigforstander: Jens Husar alias Jens Pedersen (1831-1917) - Tønnesen, Eva (Historisk Årbog for Roskilde Amt, 2019)
Den hårdtslående fattigforstander: Jens Husar alias Jens Pedersen (1831-1917)